Sort by

- Relevance
- |Time

**R**=3a^2b Since b is on the right-hand side of the equation, switch the sides so it is on the left-hand side of the equation. 3a^2b=**R**Divide each term in the equation by 3a^(2). 3a^2b/3a^2=**R**/3a^2...2 Answers · Education & Reference · 16/07/2013

1)

**r**= 4∙sin(θ)**r**= 0 for 4∙sin(θ) = 0 sin(θ) = 0 θ = 0 or θ = π**r**' = 4∙cos(θ)**r**' = 0 for 4∙cos(θ) = 0 cos...or θ = π 3 + 2∙cos(0) = 5 3 + 2∙cos(π) = -5 so**r**-max at θ = 0 Graph: http://i48.tinypic.com/doauci...1 Answers · Science & Mathematics · 22/05/2012

**r**/5 + 6/5 =**r**/7 + 8/7 7r + 42 = 5r + 40 2r = - 2**r**= - 1 Answer:**r**= - 1 Checking: - 1/5 + 6/5 = - 1/7 + 8/7 5/5 = 7/7 1 = 12 Answers · Science & Mathematics · 17/11/2010

**R**(x) = -2x³ - 7x + 14**R**(11) = -2(11)³ - 7(11) + 14**R**(11) = -2(1331) - 77 + 14**R**(11) = -2662 - 77 + 14**R**(11) = -27253 Answers · Science & Mathematics · 03/07/2008

I = e/

**R**+**r**IR = e + rR {multiply both sides by**R**} IR - rR = e {subtract rR from both sides} (I -**r**)**R**= e {factor left side}**R**= e/(I -**r**) {divide both sidea by (I -**r**)4 Answers · Science & Mathematics · 13/10/2007

f(

**r**) = |(**r**- 2)(**r**- 1)|. As a piecewise defined function f(**r**) = (**r**- 2)(**r**- 1) if**r**≤ 1 or**r**≥ 2 f(**r**) = -(**r**- 2... that f ' isn't defined at**r**= 1. f has three critical values on the...1 Answers · Science & Mathematics · 27/06/2013

lim ((a^

**r**+ b^**r**)/2)^(1/**r**) (as**r**--> 0) LN lim = lim LN lim LN ((a^**r**+ b^**r**)/2)^(1/**r**) = = lim (1/**r**)LN ((a^**r**+ b^**r**)/2) (as**r**--> 0) is...3 Answers · Science & Mathematics · 15/10/2012

1) Let L = {

**r**in**R**| ra = 0}. a) If u and v are in L then (u+v)a...b) If**r**is in**R**and u is in L then (ru)a =**r**(ua) = 0, so ru is in L, which shows that L is...1 Answers · Science & Mathematics · 22/12/2010

Complete the square

**r**^2 + 3r = 2 (**r**+ 3/2)^2 - 9/4 = 2 (**r**+ 3/2)^2 = 2 + 9/4 (**r**+ 3/2)^2 = 17/4**r**+ 3/2 = +/- Sqrt 17/4**r**= - 3/2 +/- Sqrt 17/4 If you need to go further**r**= - 3/2 + 2.0615 = 0.5615**r**= - 3/2 - 2.0615 = - 3.56151 Answers · Science & Mathematics · 16/08/2010

π(

**r**+6) ² = 15(2π**r**) + 2 πr² First, recognize that since everything on both... out of the equation entirely. π(**r**+6) ² = 15(2π**r**) + 2 πr² π(**r**+6) ² = π[15(2r) + 2r²] (**r**+6...5 Answers · Education & Reference · 20/09/2010